2021
DOI: 10.24875/rme.20000063
|View full text |Cite
|
Sign up to set email alerts
|

Effect in self-care behavior and difficulties in coping with diabetes during the COVID-19 pandemic

Abstract: In this study, difficulties in coping with diabetes were evaluated during the coronavirus disease 2019 (COVID-19) lockdown. Similarly, the change in diabetes self-care activities was evaluated in patients with a recent assessment before COVID-19 lockdown in Mexico City. In 212 patients with type REVISTA MEXICANA DE ENDOCRINOLOGÍA, METABOLISMO & NUTRICIÓN

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 14 publications
2
20
0
4
Order By: Relevance
“…Fourteen studies identified the impacts of COVID-19 on primary care service provision [ 19 , 22 , 29–33 , 35 , 36 , 38 , 42 , 44 , 45 ]. Impacts were classified under the sub-themes: reduced capacity of/access to primary care, reduced quality of primary care, and patients’ avoidance or delaying of non-COVID care.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourteen studies identified the impacts of COVID-19 on primary care service provision [ 19 , 22 , 29–33 , 35 , 36 , 38 , 42 , 44 , 45 ]. Impacts were classified under the sub-themes: reduced capacity of/access to primary care, reduced quality of primary care, and patients’ avoidance or delaying of non-COVID care.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies documented reduced capacity of/or access to primary care during the pandemic [ 22 , 29–33 , 35 , 36 , 38 , 42 ]. Reduced capacity was owing to overwhelming numbers of COVID-19 patients and staff shortages [ 29 , 31 , 33 ], restrictions on in-person consultation opportunities [ 22 , 33 ], and personal protective equipment (PPE) shortages [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…La adherencia al tratamiento se encuentra en relación con diferentes factores: socioeconómicos, del tratamiento, de la enfermedad y del sistema de salud. En un estudio realizado en la Ciudad de México durante la pandemia de COVID-19 se observó una caída del 19% en la adherencia y un incremento del 22% en los problemas relacionados con el acceso al tratamiento farmacológico 25 . En la misma línea, en nuestro estudio hallamos una reducción significativa de la adherencia al tratamiento en comparación con el año 2019.…”
Section: Discussionunclassified
“…Este primer número de la revista incluye tres artículos sobre COVID-19: desde la perspectiva ética por la Dra. María Eugenia Garay, et al 7 , el efecto de la enfermedad en las prácticas de autocuidado de los pacientes con diabetes por el Dr. Rubén Silva, et al 8 , y las recomendaciones para el manejo de pacientes con enfermedades tiroideas ante la contingencia por el grupo del Dr. Antonio Segovia 9 . Además, el Dr. Miguel Ángel Mendoza, et al nos presentan un artículo original sobre síndrome metabólico en hipotiroidismo 10 y el Dr. Enmanuel Velásquez, et al, uno sobre la adaptación y análisis psicométrico de una encuesta de conocimientos en diabetes mellitus 11 .…”
unclassified